ANALYSIS OF THE NEEDS FOR ENGLISH MATHEMATICS SUBJECTS USES ANDROID-BASED LEARNING MEDIA - Tika Septia; Rahma Wahyu (Bajang Institute, 2023)
The purpose of this research is to determine students' needs in learning media based on Android in Mathematics English lectures. The research method is quantitative with second-semester student research subjects. The instrument used in this study was a questionnaire or questionnaire, involving two indicators. The indicators for the need for facilities and learning style tendencies show that 100% of students have Android-based smartphones, and student interaction with smartphones leads to a presentation of 94.1%. It indicates that smartphone facilities are very much needed, mainly since only 29.4% of students use Android-based learning media. The questionnaire results from indicators of the tendency for student learning styles to prefer, with a percentage of 41.2% using words such as feel, touch, and hold, and 47.1% of students more easily remember things seen or read. What is done, 58% of students prefer to read than read, then 52.5% of students strongly agree, and 47.1% agree if Android-based learning media is developed. Based on the results of this study, it is necessary to establish Android-based learning media in the learning process. Results of Indicators of Facilities Needs for Android-Based Learning Media